PERSEPSI PEKERJA, MANDOR DAN KEPALA TUKANG TENTANG PENTINGNYA PELAKSANAAN SISTEM MANAJEMEN KESELAMATAN, KESEHATAN KERJA DAN LINGKUNGAN PADA PROYEK KONSTRUKSI - 92-102 . Trimailuzi (CIVED, 2013)
The objective of this research is to investigate the perception of the workers on the significance of safety management, working and environmental health in construction projects in Padang. This research is descriptive which uses the populations that consist of five major construction companies in Padang. The treatment of the samples uses quota sampling method on 45 respondents that consist of 25 workers, 10 supervisors, and 10 workers chiefs. The technique used in taking and treating the data is distributing the questioner sheets,  and interviewing the respondents. This research consists of 3 sub-variables for worker respondents as follow: planning, provision of health and safety facilities, and application. Based on the research, the result of data analysis of 3 sub-variables which show the percentage about 82% for workers, 81% for supervisors, and 80% for workers chiefs. It means that the doers in those projects have actually exercised and applied safety management system and working environmental health to reduce the numbers of working accidents and injuries. Key words :        proyek konstruksi, SMK3L, persepsi pekerja